Measurement and ab initio Investigation of Structural, Electronic, Optical, and Mechanical Properties of Sputtered Aluminum Nitride Thin Films - Alsaad, A. M.; Al-Bataineh, Qais M.; Qattan, I. A.; Ahmad, Ahmad A.; Ababneh, A.; Albataineh, Zaid; Aljarrah, Ihsan A.; Telfah, Ahmad (Frontiers in Physics, 2020)
Aluminum Nitrides (AlN) thin films have been deposited ‎on glass substrates using DC-magnetron sputtering technique for different back pressure. The piezoelectric and related properties of highly c-axis oriented AlN films fabricated by dc planar magnetron sputtering have been calculated. Experimental results show that highly c-axis oriented AlN films can be fabricated by dc planar magnetron sputtering. X-ray powder diffraction (XRD) technique shows that AlN thin films exhibit a hexagonal structure. Vienna Ab initio Simulation Package (VASP) within the framework of density functional theory (DFT) and generalized gradient approximation (GGA) was used to investigate the structural and electronic properties of hexagonal AlN structures. The experimental lattice parameters of the as prepared thin films are found to be in good agreement with ab-initio calculated parameters. UV–Vis spectrophotometer measurements are performed to investigate the optical properties of AlN thin films. We found that the refractive index of AlN thin films exhibits values ranging between 2.1 and 2.2. Furthermore, the elastic, piezoelectric and dielectric tensors of AlN crystal are calculated using VASP. The dynamical Born effective charge tensor is reported for all atoms in the unit cell of AlN. The value of the principle component of electronic contribution to the static dielectric tensor of AlN is found to be ≈ 4.68 that is in good agreement with the experimental static dielectric constant. In addition, clamped-ion piezoelectric tensor is calculated. The diagonal components of the piezoelectric tensor are found to be e_33=1.784 C/m^2 and e_31=-0.8 C/m^2. The large values of the piezoelectric coefficients show that polar AlN crystal exhibits a strong microwave piezoelectric effect. Furthermore, the components of the elastic moduli tensor are calculated. The extraordinary electronic, optical, piezoelectric and elastic properties make AlN thin films potential candidates for several opto-electronic, elastic, dielectric and piezoelectric applications.